2015
DOI: 10.1039/c5nj00787a
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth 3-(4′-hydroxyphenyl)propionate complexes

Abstract: Structural variation of lanthanoid 3-(4′-hydroxyphenyl)propionates and investigation of the anti-corrosion properties of lanthanum 3-(4′-hydroxyphenyl)propionate are presented, highlighting lanthanoid contraction and the importance of the –CHCH− structural unit of 4-hydroxycinnamates in corrosion mitigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Overall, the , RE-O . bond lengths of the aqua complexes are in excellent agreement with the corresponding values of Ce or Nd atoms of the same coordination numbers in [Ce 2 (hpp) 6 (H 2 O) 3 ] and [NaNd(hpp) 7 (H 2 O)(MeOH)] [13] complexes, where the mbp chain can be viewed as a functionalised hpp (Ligand C, Fig. 1).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Overall, the , RE-O . bond lengths of the aqua complexes are in excellent agreement with the corresponding values of Ce or Nd atoms of the same coordination numbers in [Ce 2 (hpp) 6 (H 2 O) 3 ] and [NaNd(hpp) 7 (H 2 O)(MeOH)] [13] complexes, where the mbp chain can be viewed as a functionalised hpp (Ligand C, Fig. 1).…”
Section: Resultssupporting
confidence: 72%
“…General IR spectra were collected as solid samples using an Agilent Cary 630 attenuated total reflectance (ATR-IR) spectrometer between 4000 and 600 cm À1 . 1 H and 13 Na(mbp) 3-(4 0 -Methylbenzoyl)propanoic acid (0.89 g, 4.7 mmol) was neutralised with sodium hydrogen carbonate (0.39 g, 4.7 mmol) in a mixture of ethanol (EtOH) and water (1 : 1 v/v). Upon 3486wbr, 3027vw, 2915wbr, 1695m, 1678m, 1589s, 1557s, 1433s, 1399s, 1356m, 1297m, 1256w, 1239m, 1218w, 1202m, 1179m, 1110w, 1080w, 1063w, 1038w, 1018w, 994w, 976w 3514wbr, 3463wbr, 3058vw, 3026vw, 2913wbr, 1683m, 1670m, 1605m, 1572m, 1551s, 1531s, 1518m, 1431s, 1405s, 1356m, 1300w, 1240m, 1200m, 1186m, 781w, 976w, 950w, 890m, 863w, 845w, 812s, 787w, 1695m, 1675m, 1630w, 1607m, 1572m, 1542s, 1423m, 1400s, 1356s, 1300m, 1268w, 1240m, 1203m, 1179m, 1148w, 1110w, 1078w, 1062w, 1040vw, 1011w, 991w, 970m, 894m, 884w 3460wbr, 3027vw, 2915w, 2900w, 1693m, 1675m, 1631w, 1605m, 1576s, 1553s, 1428s, 1400s, 1357s, 1295s, 1264w, 1239m, 1217vw, 1202m, 1181s, 1149vw, 1109vw, 1018w, 970w, 957w, 946vw, 886w, 855w, 813m, 807s, 791m…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, considering one Hbtec 3− anion, these coordination modes are described by each carboxylate group, separately. 55 As can be seen in Figure 5c, the Hbtec 3− ligand is simultaneously connected to five Eu III ions, acting as a μ 5 -bridging ligand and exhibiting three coordination modes: two carboxylates in a μ 2 -η 1 :η 2 chelating/bridging mode and other two carboxylate groups in η 2 chelating and η 1 monodentate fashions, as suggested by vibrational spectroscopy. The literature reports several examples of metal−organic frameworks derived from 1,2,4,5-benzenetetracarboxylic acid with transition metals, 56−60 and in less quantity with lanthanide III ions.…”
Section: Resultsmentioning
confidence: 79%
“…7,9,10 From this past work, it is evident that the aromatic carboxylate, p-coumarate, provides very efficient inhibition. 2,[11][12][13][14] For instance, when comparing lanthanum 3-(4 0 -hydroxyphenyl)propionate with lanthanum ( p-coumarate) 3 , Deacon et al demonstrated that the coumarate with the unsaturated double bond in the side group provides better surface passivation than the aliphatic propionate group. 12 In fact, it is reported that the carboxylate group has the ability to create a hydrogen bond with the hydroxide groups of the surface, that contributes to the formation of surface complexes which acts as a barrier against corrosion.…”
mentioning
confidence: 99%